Perception on Health as an indicator towards a Welfare State - Francis, Reni (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
A welfare state is a social system in which the government assumes responsibility for the well-being of citizens by making sure that people have access to basic resources such as housing, health care, education, and employment. The present study aims to find out the perception of degree college students based on Health on selected variables such as gender and socio-economic status. The aspects of health are women and child health, nutrition, disease and disorder, sanitation and hygiene and mental health. The sample for the study were 536 students, data was analyzed through ttest and ANOVA. A rating scale tool consisting of 64 statements on Health were analyzed. The findings of the study revealed significant difference of student perception on health towards a welfare state. The perception is based on gender and it has an impact on the rural and urban divide, role of government in mainstreaming the aspects that are not duly taken care off. With a huge burden of family pressure and obligations, minimum food, resources are only affordable, this inherits diseases and disorders, thus crippling the younger generation. Lack of awareness about the health hazards also could be an indicator to lack of nutrition and good habits. The sourcing medical expenses also creates hurdles to health care. The poor are often burdened with huge financial crisis due to poverty, unemployment and many times health, safety are often sidelined and given least priority. The world is witnessing unique challenges that is a threat to health and well-being of the society, the efforts of government and community are collectively responsible to the growing health hazards towards a welfare state. The growth and welfare of nation depends on the development of an individual and in taking a critical judgement for the welfare of the society. Every individual contributes to national development leading to productivity. The perception of students may be a result of stigmatization in the society due to lack of good mental health, this could be done through monitoring of people promoting health actions. Equal and fair access to health has been a core aspect of health care system in a Welfare State. The inequalities existing in a state gives a headway to the differences in Socio Economic status (SES) of the people, the higher SES leads to more improved facilities and benefits, whereas this goes on a reverse gear with the lower SES to a person needing the same care. The aim of a nation would be to decrease the gap among the rich and poor with adequate access to sanitation, hygiene, safe drinking water, free health and medical services, upliftment of women and their health care, responsive government actions thus making it favorable towards a welfare state.